2019
DOI: 10.3390/ani9070428
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Health Benefits of Guide Dog Ownership in an Austrian Population of Blind People with and without a Guide Dog

Abstract: Blindness has previously been associated with impaired quality of life (QOL). Guide dogs may not only support blind people in their independency, but also facilitate social relationships and overall health. This study sought to investigate whether blind people from Austria with a guide dog, when compared with blind people without a guide dog, differ in their QOL, annual medical costs, and attitudes towards the human–guide dog relationship. Participants (n = 36) filled out an online accessible questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(79 reference statements)
0
11
0
1
Order By: Relevance
“…Egy később megjelent tanulmány azonban cáfolja ezeket az állításokat. Eszerint a vakvezetőkutya jelenléte nem társult jobb életminőséggel (Glenk, Přibylová, Stetina, Demirel, & Weissenbacher, 2019). McIver, Hall és Mills (2020) tanulmánya szembe megy ezzel az állítással, eredményeik alapján a vakvezetőkutyát használó személyek az idő múlásával életminőségbeli javulást, növekedést mutatnak.…”
Section: ] Rendelet)unclassified
“…Egy később megjelent tanulmány azonban cáfolja ezeket az állításokat. Eszerint a vakvezetőkutya jelenléte nem társult jobb életminőséggel (Glenk, Přibylová, Stetina, Demirel, & Weissenbacher, 2019). McIver, Hall és Mills (2020) tanulmánya szembe megy ezzel az állítással, eredményeik alapján a vakvezetőkutyát használó személyek az idő múlásával életminőségbeli javulást, növekedést mutatnak.…”
Section: ] Rendelet)unclassified
“…Thus, research has demonstrated a number of benefits to owning a guide dog in day-to-day life, such as increased mobility, independence, confidence and social interaction (Tomkins et al, 2011;Audrestch et al, 2015;Gravrok et al, 2018). Indeed, more recent research indicates a preference for the use of guide dogs as a mobility aid, as opposed to the white cane or more modern alternatives among vision impaired persons (Glenk et al, 2019). Yet, challenges remain for guide dog owners as they struggle to locate appropriate facilities for their dogs and the role of the guide dog is also typically misunderstood by the general public (Mesquita & Corneira, 2016).…”
Section: Guide Dogs For People With Vision Impairmentmentioning
confidence: 99%
“…The biggest challenge for PwVI, once at the destination, is wayfinding (Bosch & Gharaveis, 2017). Recent research suggests that guide dog owners prefer to work their guide dogs, even in unfamiliar places, as they are perceived to be faster and safer mobility aids, as opposed to the white cane or technological alternatives (Glenk et al, 2019). Additionally, the very presence of their guide dog adds comfort, companionship, confidence and a sense of independence.…”
Section: At the Destinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are already numerous technical aids, guide dog handlers prefer their dogs to these aids [ 2 ]. Many guide dogs are also considered part of the family [ 3 ]. For the aforementioned reasons, and also due to the expensive and time-consuming training of a guide dog, it is important that a guide dog can complete a long and, above all, healthy service.…”
Section: Introductionmentioning
confidence: 99%